Moda, história e política: a moda como meio de legitimação da causa LGBTQ, usando como referencial a naturalidade da homossexualidade na Grécia antiga. - Alves, Jean Matheus Dias do Nascimento (Universidade do Vale do Rio dos Sinos, 2021)
This study aims to discuss and highlight the role of the LGBTQ community as a promoter of causes and values for fashion, from a historical perspective of homosexuality in ancient Greece and its legitimacy for the Hellenic people. Homosexuality has not always been marginalized as it is today, the Occident has gone through many changes. Many values have been transformed, others have been lost, and there are those that have been destroyed. Deepening in Greek aesthetic values, understanding pederasty, getting to know the body of the Hellenic citizen, their vanities, jewelry and unveiling desire and sex through Greek clothing, we will reach post-modernity and activist agendas around the LGBTQ community. Thus, from a fashion point of view and perspective, this work will discuss about gay activism, bringing a dialogue about the power of fashion as a communicator and social driver of values and will promote a fashion collection that, through its pieces ,bring a reflection about the central social problem, which is homophobia.
Keywords: Moda; Homossexualidade; Grécia antiga; Ativismo; Homofobia; Fashion; Homossexuality; Ancient Greece; Activism